Political Values of Kharkov Inhabitants: Practices, Knowledge, Orders - Golikov, Alexander (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2018)
The article analyzes the political values of the residents of Kharkiv. On the basis of «synthetic» theories’ methodology (primarily P. Bourdieu), as well as the researches of major theorists and empiricists in the field of political culture (Deutsch, Almond, Verba, Inglehart), the author explores the connection of political values with practices and structures of knowledge about politics (such such as expectations, awareness, preferences, etc.). Based on the results of an empirical study conducted in December 2017 by a team of Sociology Department of the V.N. Karazin Kharkiv National University, author describes the differentiation of political values among Kharkiv citizens. Contradictions and collisions within the structures of political values are demonstrated, various groups of Kharkiv citizens are distinguished depending on political values. A final platoon that political identities, knowledge and practices constitute a single complex internally connected by complex relationships is being formulated.